Fabrication of phospholipid–xanthan microcapsules by combining microfluidics with self-assembly - Mendes, A. C. (2013)
We report the synthesis of an amphiphilic polysaccharide, a phospholipid (1,2-dioleoyl-sn-glycerophosphoetilamine, DOPE) conjugated with the anionic xanthan gum, and its ability to spontaneously self-assemble under mild aqueous conditions. This work also aimed to apply a microfluidic platform that can precisely fabricate microsized and monodispersed capsules for cell encapsulation. Stable hollow capsular structures were obtained by the generation of homogeneous spherical droplets of the selfassembled polymer in the microfluidic device through the formation of a water-in-oil emulsion, followed by the stabilization of the polymer aggregates in a separate collection vessel containing phosphatebuffered saline (physiological ionic strength and pH). The properties (size, morphology, permeability) and performance (stability) of the obtained microcapsules were studied, as well their ability to support the viability, function and proliferation of encapsulated cells. ATDC5 cells were encapsulated within the capsules and shown to remain viable, evidencing increased cellular metabolic activity over 21 days of in vitro culture. By combining microfluidic droplet generation and self-assembly of xanthan–DOPE, we were able to fabricate microcapsules that provided an adequate environment for cells to survive and proliferate.